(untitled) (In situ, 2024)
Several rescaue research campains of the shipwreck off the rock of Mali Školj in the bay of Suđurađ on the island of Šipan was carried out from 1972 to 1974. More than three decades later, it was confirmed that the sunken ship is Santo Hieronimo, which belonged to the Dubrovnik businessman Jerolim Benedikt Primojević and sank in 1576. Systematic research began in 2015, and by 2023 it covered the surface from the bow part of the ship, along the keel, to the central part of the ship.